2010
DOI: 10.1111/j.1365-2486.2010.02345.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of nitrogen deposition on species composition change in calcareous grasslands

Abstract: Atmospheric nitrogen (N) deposition has been identified as a major threat to biodiversity, but field surveys of its effects have rarely focussed on sites which are actively managed to maintain characteristic species. We analysed permanent quadrat data from 106 plots in nature reserves on calcareous grassland sites in the UK collected during a survey between 1990 and 1993 and compared the data with the results from re-survey of 48 of these plots between 2006 and 2009. N deposition showed no significant spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
48
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(57 citation statements)
references
References 44 publications
7
48
0
2
Order By: Relevance
“…They went on to hypothesise that the composition of calcareous grassland was more likely to be affected negatively by changes to management and land use, a view shared by both Wilson et al (1995) and Jacquemyn et al (2003) who found no and minimal effects, respectively, relating to N deposition, with grazing management viewed as the primary means of regulating the composition and diversity of chalk grassland. Van den Berg et al (2011) found no correlation between N deposition and a change in Ellenberg N values, but did find that a decrease in grazing pressure was significantly negatively correlated to a change in diversity (see also Walker et al 2009). …”
Section: Species Richnessmentioning
confidence: 95%
See 1 more Smart Citation
“…They went on to hypothesise that the composition of calcareous grassland was more likely to be affected negatively by changes to management and land use, a view shared by both Wilson et al (1995) and Jacquemyn et al (2003) who found no and minimal effects, respectively, relating to N deposition, with grazing management viewed as the primary means of regulating the composition and diversity of chalk grassland. Van den Berg et al (2011) found no correlation between N deposition and a change in Ellenberg N values, but did find that a decrease in grazing pressure was significantly negatively correlated to a change in diversity (see also Walker et al 2009). …”
Section: Species Richnessmentioning
confidence: 95%
“…For example, a survey of Pulsatilla vulgaris sites in lowland England undertaken by Wells (1968) and repeated by Walker and Pinches (2011) recorded a decline in the distribution of P. vulgaris correlated with reduced grazing at sites previously supporting short, herb-rich swards. Van den Berg et al (2011) re-surveyed permanent quadrat data from the early 1990s to understand better the effects of atmospheric nitrogen (N) deposition on species-rich calcareous grassland sites, finding significant associations with high deposition and changes in Shannon diversity, evenness and a decline in the frequency of characteristic species. Bennie et al (2006) re-visited calcareous grassland plots first surveyed in the early 1950s, finding that although there was a general reduction in species richness and a shift to more mesotrophic vegetation, plots located on steep, south-facing slopes with shallow rendzina soils were more resilient to the spread of competitive species compared with communities of deeper soils, due to phosphorus limitation and an increased frequency and magnitude of drought events.…”
mentioning
confidence: 99%
“…Herbivores are known to increase ANPP due to FIG. The reason for this change is not clear, but could be related to the sharp increase in ammonium concentrations in the soil after the liquid mixture of dung and urine was applied in 2011, which may have toxic effects on plant growth due to acidification of soil (Van Den Berg et al 2011, Chen et al 2013). Effects of dung and urine return, mowing, and trampling on the quality of litter and roots at the end of the growing season in 2012.…”
Section: Grazing and Plant Parametersmentioning
confidence: 99%
“…Forest inventories (mainly started up in the 1980s) and phytosociological studies providing valuable ancient floristic information (e.g., Braun, 1915) represent an important background to long-term research for detecting the impacts of longrange air pollution on vegetation. Previous studies have shown significant shifts in the forest herb layer due to acidification (Diekmann & Dupré, 1997;Baeten et al, 2009;Van Den Berg et al, 2011). Previous studies have shown significant shifts in the forest herb layer due to acidification (Diekmann & Dupré, 1997;Baeten et al, 2009;Van Den Berg et al, 2011).…”
Section: Introductionmentioning
confidence: 98%